National and subnational plans for primary prevention and early detection of oral and oropharyngeal cancer: a scoping review - Marcia Frias Pinto Marinho; Maria Clara Frias Lobo Marinho; Guido Artemio Marañón-Vásquez; Keith Bullia da Fonseca Simas; Mário José Romañach; Aline Corrêa Abrahão; Maria Augusta Visconti Rocha Pinto; Lucianne Cople Maia de Faria; Michelle Agostini (Cadernos de Saúde Pública)
This scoping review maps primary prevention and early detection strategies for oral and oropharyngeal cancer across national cancer plans and noncommunicable disease plans from all World Health Organization Member States. Following PRISMA-ScR guidelines, bibliographic search was performed on key organization websites until March 2023. Of the 194 countries assessed three had subnational plans, resulting in 264 self-governing political entities and similar with revised plans. Among these, 124 (47%) addressed oral and oropharyngeal cancer risk factors and preventive strategies, including 73 national and 51 subnational plans (one from Australia, two from the United Kingdom and 48 from the United States) across 76 (39.2%) countries. Southeast Asia led with 81.8% self-governing political entities mentioning oral and oropharyngeal cancer risk factors and preventive strategies, followed by the Americas (63.5%). Western Pacific and Eastern Mediterranean regions had the lowest coverage with 24.2% and 23.8%, respectively. Tobacco use was the most discussed oral and oropharyngeal cancer risk factor in primary prevention plans (63.7%), followed by HPV infection (54%) and alcohol consumption (35.5%). Opportunistic examination was the most common strategy for early detection, recommended by 29% of self-governing political entities, followed by screening in high-risk individuals (14.5%), self-examination (5.6%), and population-based screening (2.4%). Despite the high oral and oropharyngeal cancer incidence in many countries, most cancer plans only indirectly covered it and showed a great diversity of preventive strategies. Missing data in available documents should not imply an absence of an oral and oropharyngeal cancer policy. Other documents may exist but were not available on the websites, highlighting potential bias.